Stem Cells and Exosomes Delivery via Collagen-Based Platform for Advanced Wound Healing: A Systematic Review of In Vivo Studies - Ratih Paramita Suprapto; Raras, Tri Yudani Mardining; Kusuma, Ihda Dian (Fakultas Kedokteran Universitas Brawijaya, 2026)
Chronic wounds remain a global health challenge due to persistent inflammation and impaired cellular function that delay healing. Collagen-based hydrogels are promising delivery platforms for enhancing the therapeutic efficacy of mesenchymal stem cells (MSCs) and exosomes. This review aimed to evaluate the efficacy and molecular mechanisms of MSCs and/or their derived exosomes delivered in collagen-based hydrogels in accelerating wound healing in vivo. This review was managed following PRISMA 2020 guidelines. Literature searches were conducted in PubMed, Scopus, and Europe PMC for original studies published between 2020 and 2025. Eligible studies provided sufficient data describing in vivo chronic wound models treated with collagen scaffolds loaded with MSCs or exosomes. Three in vivo studies using murine burn, diabetic rat, and diabetic rabbit models were included. Each of them used pullulan-collagen seeded with Adipocyte Stem Cells (ASCs), stem cell-derived exosomes combined with recombinant human collagen-methacrylate, and MSC-derived extracellular vesicles (EVs) loaded into collagen hydrogel. All platforms significantly accelerated wound closure versus controls. Histological analyses confirmed enhanced neovascularization, organized collagen deposition, mature granulation tissue formation, and re-epithelization. These effects were mediated by M1-to-M2 macrophage polarization and downregulation of pro-inflammatory cytokines. Cell-free exosome therapy loaded in collagen hydrogels represents a promising approach for chronic wound management.